2015
DOI: 10.1093/cercor/bhv308
|View full text |Cite
|
Sign up to set email alerts
|

The Corticocortical Structural Connectivity of the Human Insula

Abstract: The insula is a complex structure involved in a wide range of functions. Tracing studies on nonhuman primates reveal a wide array of cortical connections in the frontal (orbitofrontal and prefrontal cortices, cingulate areas and supplementary motor area), parietal (primary and secondary somatosensory cortices) and temporal (temporal pole, auditory, prorhinal and entorhinal cortices) lobes. However, recent human tractography studies have not observed connections between the insula and the cingulate cortices, al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
192
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 252 publications
(209 citation statements)
references
References 104 publications
14
192
1
2
Order By: Relevance
“…Insula also predicts the probability of adverse outcomes from behavior choices (Preuschoff et al, 2008). Moreover, insula enjoys connections with almost every other site listed in Table 2 (Ghaziri et al, 2015), suggesting a role in coordinating those sites.…”
Section: Discussionmentioning
confidence: 99%
“…Insula also predicts the probability of adverse outcomes from behavior choices (Preuschoff et al, 2008). Moreover, insula enjoys connections with almost every other site listed in Table 2 (Ghaziri et al, 2015), suggesting a role in coordinating those sites.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoconnectivity within the insula has been previously reported and hypothesized as playing a role in alcohol relapse because of a diminished awareness of substance use (Camchong et al, 2012). Another possible explanation for the observed hypo-connectivity is the known damage to white matter caused by alcohol (Pfefferbaum et al, 2000) which disrupts the anatomical connection between left insula and lingual gyrus (Ghaziri et al, 2015). The insula and the putamen are regions that has been previously associated with the brain reward system and with different directions of effects including loss of connectivity (Kuceyeski et al, 2013) and increased connectivity (Zhu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported joint activity in these regions for tasks requiring self-judgment (Araujo et al, 2013) and social comparison (Beer & Hughes, 2010;Kedia, Lindner, Mussweiler, Ihssen, & Linden, 2013;Lindner et al, 2015;Moore et al, 2014). Moreover, research shows that these brain areas are structurally (Ghaziri et al, 2017) and functionally connected to each other (Cauda et al, 2012(Cauda et al, , 2011Dosenbach et al, 2006;Penner et al, 2016;Sridharan, Levitin, & Menon, 2008;Taylor, Seminowicz, & Davis, 2009). Therefore, we combined the values obtained for each of these ROIs in a 5 (region: AI, vACC, dACC, VMPFC, & DMPFC) × 2 (hemisphere: left vs right) × 2 (targets: self-other vs familiar-other) × 2 (direction: upward vs downward) × 2 (distance: high vs low) repeated measure ANOVA.…”
Section: Fmri Data: Roi Analysesmentioning
confidence: 94%